Solid waste-based ceramsite and method of making same
Patent Information
- Application Number
- CN202510500644.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-21
- Publication Date
- 2026-10-23
AI Technical Summary
[0033]本发明的固废基陶粒和制备方法,利用煤矸石、气化细渣等煤基固废为原料,在低温、低能耗条件下即可制备得到性能好的固废基陶粒;综合考虑了固废原料替代、固废自身性能等方面,将原料成分性能与煅烧过程结合,通过整个过程的烘干段节能、预热段节能(对应一次煅烧)、煅烧段节能(对应二次煅烧)、冷却段节能四个环节分别降耗节能,实现了固废基陶粒的低温、低能耗制备。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid waste-based ceramsite, specifically relating to solid waste-based ceramsite and its preparation method. Background Technology
[0002] Under the national trend of promoting green environmental protection and sustainable development, prefabricated construction, sponge cities, and the ban on sand and gravel mining have increased both the usage and demand of expanded clay aggregate (ECA). Simultaneously, the raw material sector for ECA is facing significant changes, with the use of raw materials such as clay and shale gradually being restricted, leading to a greater reliance on solid waste as a raw material source. The energy consumption and emissions associated with the large-scale utilization of solid waste will receive considerable attention: on the one hand, the large amount of solid waste incorporated results in higher energy consumption in ECA production compared to traditional raw materials. On the other hand, solid waste contains a high content of inorganic mineral phases, often resulting in sintered ECA, which requires high-temperature firing to ensure strength and low water absorption. High-temperature heat preservation further increases energy consumption. Furthermore, the firing process requires multiple stages of heat preservation, sometimes necessitating two or more machines to complete the firing process simultaneously, ensuring the production of stable ECA, thus further increasing the energy consumption of ECA production.
[0003] Currently, there is relatively little attention and research on reducing energy consumption and corresponding environmental protection measures in the production of expanded clay aggregate. Under the trend of green and sustainable development, reducing energy consumption in expanded clay aggregate production, thereby lowering production and environmental costs, is an urgent issue that needs to be addressed. Summary of the Invention
[0004] The first objective of this invention is to provide a solid waste-based ceramsite, which is prepared from solid waste as raw material, and the preparation process is low-temperature, low-energy consumption, and has good performance.
[0005] The second objective of this invention is to provide a method for preparing the aforementioned solid waste-based ceramsite.
[0006] To achieve the first objective of this invention, the following technical solution is adopted:
[0007] A solid waste-based ceramsite, the raw materials for which are prepared include the following substances in parts by weight:
[0008] Aluminosilicate mineral materials 70-95;
[0009] Carbon-silicon composite material 4-29;
[0010] Pore conditioner 1-10;
[0011] Raw material expansion agent 1-30.
[0012] Preferably, the raw materials for preparing the solid waste-based ceramsite of the present invention further include a plasticity modifier, wherein the plasticity modifier is ≤10 parts by weight.
[0013] Preferably, in the solid waste-based ceramsite of the present invention, the content ratio of SiO2 / Al2O3 in the silica-alumina mineral material is ≥1.2, and / or the total content of SiO2 and Al2O3 is ≥70%; and / or the total carbon content is ≤15%, and / or the organic matter content is ≥4%.
[0014] The solid waste-based ceramsite of the present invention preferably includes, in combination, one or more of the following: coal gangue, kaolin, and bentonite.
[0015] In the solid waste-based ceramsite of the present invention, preferably, the total dry SiO2 content in the carbon-silicon composite material is ≥30%, and / or the carbon content is ≥15%, and / or the iron oxide content is ≥3%.
[0016] The solid waste-based ceramsite of the present invention preferably includes a combination of one or more of the following: gasification fine slag, high-carbon coal gangue, coal slime, and silicon carbide.
[0017] In the solid waste-based ceramsite of the present invention, preferably, the plasticity modifier has a plasticity index ≥10 and / or a particle size D. 90 ≤100μm, and / or the calcium oxide content therein is ≥3%.
[0018] In the solid waste-based ceramsite of the present invention, preferably, the plasticity modifier includes slag and / or clay.
[0019] In the solid waste-based ceramsite of the present invention, preferably, the pore conditioner includes a first pore conditioner and / or a second pore conditioner;
[0020] The first pore conditioner contains ≥10% Fe2O3; and / or the first pore conditioner includes red mud and / or hematite;
[0021] The second pore conditioner includes carbonates.
[0022] In the solid waste-based ceramsite of the present invention, preferably, the raw material expansion agent comprises water and / or an aqueous solution of a water-reducing agent.
[0023] To achieve the second objective of this invention, a method for preparing the aforementioned solid waste-based ceramsite is also provided, the method comprising:
[0024] (1) After crushing and grinding all the raw materials except the raw material expansive agent, they are mixed according to the weight ratio to obtain a mixture;
[0025] (2) The mixture obtained in step (1) is mixed with the raw material expansion agent according to the weight ratio, granulated and polished to obtain ceramsite raw material balls;
[0026] (3) The ceramsite raw material balls obtained in step (2) are dried to obtain dried raw material balls;
[0027] (4) The dried raw material balls obtained in step (3) are calcined to obtain solid waste-based ceramic particles.
[0028] In the preparation method of the present invention, preferably, in step (3), the drying treatment is to place the ceramsite raw material balls obtained in step (2) in an oven at 40-70℃ for 4-24 hours.
[0029] In the preparation method of the present invention, preferably, in step (4), the calcination treatment includes a first stage and a second stage;
[0030] In the first stage, the calcination temperature is 300-500℃, and / or the calcination time is 10-90 min; and / or the heating rate is 3-5℃ / min; and / or,
[0031] In the second stage, the calcination temperature is 700-1000℃, and / or the calcination time is 30-90 min; and / or the heating rate is 5-15℃ / min.
[0032] The beneficial effects of this invention are as follows:
[0033] The solid waste-based ceramsite and its preparation method of the present invention utilize coal-based solid wastes such as coal gangue and gasification slag as raw materials, and can prepare high-performance solid waste-based ceramsite under low temperature and low energy consumption conditions. Taking into account the substitution of solid waste raw materials and the properties of the solid waste itself, the raw material composition and properties are combined with the calcination process. Energy saving is achieved through four stages of energy saving in the drying stage, the preheating stage (corresponding to the first calcination), the calcination stage (corresponding to the second calcination), and the cooling stage. This enables the low-temperature and low-energy preparation of solid waste-based ceramsite. Detailed Implementation
[0034] The technical solution and its effects of the present invention will be further described below with reference to specific embodiments / examples. The following embodiments / examples are only for illustrating the content of the present invention, and the invention is not limited to the following embodiments or examples. Simple modifications made to the present invention based on the concept of the present invention are all within the scope of protection claimed by the present invention.
[0035] This invention provides a solid waste-based ceramsite, the raw materials for which include the following substances in parts by weight:
[0036] Aluminosilicate mineral materials 70-95, such as 70, 75, 80, 85, 90 and 95, as well as any value and range within this range;
[0037] Carbon-silicon composite materials 4-29, such as 4, 5, 10, 15, 20, 25 and 29, and any values and ranges within this range;
[0038] Pore conditioners 1-10, such as 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10, and any values and ranges within this range;
[0039] Raw material expansive agent 1-30, such as 1, 5, 10, 15, 20, 25 and 30, and any value and range within this range.
[0040] The solid waste-based ceramsite and its preparation method of the present invention utilize coal-based solid wastes such as coal gangue and gasification slag as raw materials, and can prepare high-performance solid waste-based ceramsite under low temperature and low energy consumption conditions. Taking into account the substitution of solid waste raw materials and the properties of the solid waste itself, the raw material composition and properties are combined with the calcination process. Energy consumption is reduced in four stages of the entire process: drying section, preheating section, calcination section, and cooling section. This achieves low temperature and low energy consumption preparation of solid waste-based ceramsite.
[0041] In one embodiment, the raw materials further include a plasticizer, wherein the plasticizer has a weight percentage of ≤10, such as 10, 9, 8, 7, 6, 5, 4, 3, 2, 1, 0.5, 0.1, 0.05, 0.01, etc., and any value and range within this range.
[0042] In one embodiment, the silica-alumina mineral material has a SiO2 / Al2O3 content ratio ≥ 1.2, such as 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 3, 5, 10, etc., and any value and range within this range; and / or the total SiO2 and Al2O3 content ≥ 70%, such as 70%, 75%, 80%, 85%, 90%, 95%, 91%, 92%, etc., and any value and range within this range; and / or the total carbon content ≤ 15%, such as 15%, 12%, 10%, 8%, 5%, 4%, 3%, 2%, 1%, etc., and any value and range within this range; and / or the organic matter content ≥ 4%, such as 4%, 5%, 10%, 15%, 20%, etc., and any value and range within this range.
[0043] In one embodiment, the silica-alumina mineral material has a SiO2 / Al2O3 content ratio of 1.2-5.5, such as 1.2, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, and 5.5, and any value or range within this range; and / or the total content of SiO2 and Al2O3 is 70-95%, such as 70%, 75%, 80%, 85%, 90%, and 95%, and any value or range within this range; and / or the total carbon content is 4-15%, such as 15%, 12%, 10%, 8%, 5%, and 4%, and any value or range within this range; and / or the organic matter content is 4-12%, such as 4%, 5%, 8%, 10%, and 12%, and any value or range within this range.
[0044] In one embodiment, the silica-alumina mineral material includes any one or a combination of coal gangue, kaolin, and bentonite.
[0045] In one embodiment, the total dry-based SiO2 content in the carbon-silicon composite material is ≥30%, such as 30%, 35%, 40%, 45%, 50%, 60%, etc., and any value and range within this range; and / or the carbon content is ≥15%, such as 15%, 18%, 20%, 25%, 30%, 35%, 40%, etc., and any value and range within this range; and / or the iron oxide content is ≥3%, 5%, 8%, 10%, 15%, 20%, etc., and any value and range within this range.
[0046] In one embodiment, the total dry-basis SiO2 content in the carbon-silicon composite material is 30-50%, such as 30%, 35%, 40%, 45%, and 50%, and any value and range within that range; and / or the carbon content is 15-35%, such as 15%, 18%, 20%, 25%, 30%, and 35%, and any value and range within that range; and / or the iron oxide content is 3-10%, 5%, 8%, and 10%, and any value and range within that range.
[0047] In one embodiment, the carbon-silicon composite material comprises any one or more combinations of gasification slag, high-carbon coal gangue, coal slime, and silicon carbide.
[0048] In one embodiment, the plasticity modifier has a plasticity index ≥10, such as 10, 11, 12, 13, 14, 15, 16, 18, 20, 25, and 30, and any value and range within that range; and / or its particle size D. 90≤100μm, such as 100μm, 95μm, 90μm, 85μm, 80μm, 75μm, 70μm, 50μm, 20μm, etc., and any value and range within this range; and / or the content of calcium oxide is ≥3%, such as 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20%, etc., and any value and range within this range.
[0049] In one embodiment, the plasticity modifier has a plasticity index of 10-26, such as 10, 11, 12, 13, 14, 15, 16, 18, 20, 25, and 26, and any value and range within that range; and / or its particle size D. 90 The thickness is 45-100 μm, such as 100 μm, 95 μm, 90 μm, 85 μm, 80 μm, 75 μm, 70 μm, 50 μm and 45 μm and any value and range within this range; and / or the calcium oxide content is 3-10%, such as 3%, 4%, 5%, 6%, 7%, 8%, 9% and 10% and any value and range within this range.
[0050] In one embodiment, the plasticity modifier comprises slag and / or clay.
[0051] In one embodiment, the pore conditioner includes a first pore conditioner and / or a second pore conditioner;
[0052] The first pore conditioner contains ≥10% Fe2O3, such as 10%, 12%, 15%, 18%, 20%, 25%, 30%, 35%, 40%, etc., and any value and range within this range; and / or the first pore conditioner includes red mud and / or hematite;
[0053] The second pore conditioner includes carbonates, such as sodium carbonate and / or calcium carbonate.
[0054] In one embodiment, the Fe2O3 content in the first pore conditioner is 10-25%, such as 10%, 12%, 15%, 18%, 20%, and 25%, as well as any value and range within that range.
[0055] In one embodiment, the pore regulator is a first pore regulator, which can not only increase the porosity, but also further reduce the melting temperature of the ceramsite system by utilizing its high iron content, thereby reducing energy consumption.
[0056] In one embodiment, the raw material expansive agent comprises water and / or an aqueous solution of a water-reducing agent.
[0057] In one embodiment, the water-reducing agent aqueous solution includes a polycarboxylate water-reducing agent aqueous solution (concentration range generally 8-20%, such as 8%, 10%, 12%, 14%, 16%, 18%, and 20%, and any value and range within this range) and / or a naphthalene-based water-reducing agent aqueous solution (concentration range generally 28-35%, such as 28%, 30%, 32%, 34%, and 35%, and any value and range within this range).
[0058] In one embodiment, the bulk density of the solid waste-based ceramsite is 800-1000 kg / m³. 3 .
[0059] In one embodiment, the compressive strength of the solid waste-based ceramsite is 5-20 MPa.
[0060] In one embodiment, the water absorption rate of the solid waste-based ceramsite is ≤20%.
[0061] The present invention also provides a method for preparing the aforementioned solid waste-based ceramsite, the method comprising:
[0062] (1) After crushing and grinding all the raw materials except the raw material expansive agent, they are mixed according to the weight ratio to obtain a mixture;
[0063] (2) The mixture obtained in step (1) is mixed with the raw material expansion agent according to the weight ratio, granulated and polished to obtain ceramsite raw material balls;
[0064] (3) The ceramsite raw material balls obtained in step (2) are dried to obtain dried raw material balls;
[0065] (4) The dried raw material balls obtained in step (3) are calcined to obtain solid waste-based ceramic particles.
[0066] In one embodiment, in step (1), the material is crushed and ground to a mesh size of less than 150 mesh.
[0067] In step (1) of the present invention, the mixing can be carried out in conventional mixing equipment in the art, such as a mixer, as long as the mixing is uniform.
[0068] In step (2) of the present invention, granulation can be carried out in conventional granulation equipment in the art, such as a granulator, such as an extrusion granulator or a disc granulator.
[0069] In step (2) of this invention, polishing is a conventional operation in the art.
[0070] To improve the drying effect, in one embodiment, the drying conditions in step (3) include: a drying temperature of 40-70℃, such as 40℃, 45℃, 50℃, 55℃, 60℃, 65℃ and 70℃ and any value and range within this range; and a drying time of 4-24h, such as 4h, 8h, 12h, 16h, 20h and 24h and any value and range within this range.
[0071] In a preferred embodiment, in step (3), the drying process involves placing the ceramsite raw pellets obtained in step (2) in an oven and drying them at 40-70°C (e.g., 40°C, 45°C, 50°C, 55°C, 60°C, 65°C and 70°C and any value and range within that range) for 4-24 hours (e.g., 4 hours, 8 hours, 12 hours, 16 hours, 20 hours and 24 hours and any value and range within that range).
[0072] Those skilled in the art will understand that in step (4), the calcination process is carried out in a calcination apparatus. In one embodiment, in step (4), the calcination process is carried out in a muffle furnace or a rotary kiln.
[0073] In order to improve the calcination effect, in one embodiment, step (4) includes a first stage and a second stage of calcination treatment;
[0074] In the first stage, the calcination temperature is 300-500℃, such as 300℃, 350℃, 400℃, 450℃, and 500℃, and any value or range within this range; and / or the calcination time is 10-90 min, such as 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, and 90 min, and any value or range within this range; and / or the heating rate is 3-5℃ / min, such as 3℃ / min, 3.5℃ / min, 4℃ / min, 4.5℃ / min, and 5℃ / min, and any value or range within this range; and / or,
[0075] In the second stage, the calcination temperature is 700-1000℃, such as 700℃, 750℃, 800℃, 850℃, 900℃, 950℃ and 1000℃, and any value and range within this range; and / or the calcination time is 30-90min, such as 30min, 40min, 50min, 60min, 70min, 80min and 90min, and any value and range within this range; and / or the heating rate is 5-15℃ / min, such as 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min, 10℃ / min, 11℃ / min, 12℃ / min, 13℃ / min, 14℃ / min and 15℃ / min, and any value and range within this range.
[0076] In a preferred embodiment, in step (4),
[0077] The first stage involves increasing the temperature at 3-5℃ / min (e.g., 3℃ / min, 3.5℃ / min, 4℃ / min, 4.5℃ / min, and 5℃ / min, and any value or range within this range) until reaching 300-500℃ (e.g., 300℃, 350℃, 400℃, 450℃, and 500℃, and any value or range within this range). Heating is then stopped, and the second stage is performed after 10-90 minutes (e.g., 3℃ / min, 3.5℃ / min, 4℃ / min, 4.5℃ / min, and 5℃ / min, and any value or range within this range); and / or
[0078] The second stage involves heating at a rate of 5-15℃ / min (e.g., 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min, 10℃ / min, 11℃ / min, 12℃ / min, 13℃ / min, 14℃ / min, and 15℃ / min, and any value or range within this range) until reaching 700-1000℃ (e.g., 700℃, 750℃, 800℃, 850℃, 900℃, 950℃, and 1000℃, and any value or range within this range). Heating is then stopped after 30-90 minutes (e.g., 30 minutes, 40 minutes, 50 minutes, 60 minutes, 70 minutes, 80 minutes, and 90 minutes, and any value or range within this range). The product is then removed from the furnace or cooled in the furnace to obtain solid waste-based ceramsite.
[0079] Those skilled in the art will understand that after calcination, cooling to room temperature is sufficient.
[0080] The solid waste-based ceramsite and its preparation method of the present invention utilize coal-based solid wastes such as coal gangue and gasification slag as raw materials, and can prepare high-performance solid waste-based ceramsite under low temperature and low energy consumption conditions. Taking into account the substitution of solid waste raw materials and the properties of the solid waste itself, the raw material composition and properties are combined with the calcination process. Energy consumption is reduced in four stages of the entire process: drying section, preheating section, calcination section, and cooling section. This achieves low temperature and low energy consumption preparation of solid waste-based ceramsite.
[0081] The solid waste-based ceramsite of this invention utilizes the aluminum-silicon component in the aluminum-silicon mineral material to provide the ceramsite framework, and the aluminum-silicon ratio can be controlled to minimize the melting point. Simultaneously, the organic matter in the aluminum-silicon mineral material releases combustible gases at high temperatures, creating pores and providing energy, achieving the first energy saving. The carbon-silicon composite material contains carbon, which can oxidize and create pores and provide energy through combustion in the calcination stage, achieving the second energy saving. The iron oxide in the pore regulator lowers the melting point of the aluminum-silicon system, ensuring that ceramsite can be calcined at a lower temperature, achieving the third energy saving. The raw material expansion agent can form primary expansion with the mica and other layered substances contained in the aluminum-silicon material, increasing the porosity of the ceramsite raw material spheres. To ensure that the reaction water is not forcibly removed, the drying stage uses a low-temperature volatilization process of 40-70℃, achieving the fourth energy saving. The overall design and coordination from formulation to drying to calcination achieves energy reduction in multiple stages while producing high-quality ceramsite.
[0082] The following examples further illustrate the content of the present invention.
[0083] Raw materials used in the following examples / comparative examples:
[0084] 1. Aluminum-silicon mineral materials:
[0085] 1) Coal gangue, with a total SiO2 and Al2O3 content of 75.0%, SiO2 / Al2O3 = 2.50, a total carbon content of 9.11%, and an organic matter content of 9.31%;
[0086] 2) Coal gangue, with a total SiO2 and Al2O3 content of 75.1%, SiO2 / Al2O3 = 2.51, a total carbon content of 6.43%, and an organic matter content of 2.18%;
[0087] 2) Kaolin, with a total SiO2 and Al2O3 content of 95%, SiO2 / Al2O3 = 1.2, total carbon content of 2.54%, and organic matter content of 5.89%;
[0088] 3) Bentonite, with a total SiO2 and Al2O3 content of 86%, SiO2 / Al2O3 = 3.9, a total carbon content of 1.59%, and an organic matter content of 4.76%;
[0089] 2. Carbon-silicon composite materials:
[0090] 1) Gasification slag, dry basis: SiO2 content 30.6%; carbon content 31.2%; Fe2O3 content 7.7%;
[0091] 2) High-carbon coal gangue, with a dry basis SiO2 content of 47.2%, carbon content of 28%, and Fe2O3 content of 3%.
[0092] 3) Coal slime, dry basis: SiO2 content 52.4%; carbon content 15%; Fe2O3 content 3.5%;
[0093] 3. Plasticity modifiers:
[0094] 1) Slag, plasticity index 12, D 90 =25μm;
[0095] 2) Clay, plasticity index 17, D 90 =75μm;
[0096] 4. Pore conditioner:
[0097] 1) Red mud, Fe2O3 content 21.0%;
[0098] 2) Hematite, Fe2O3 content 28.6%;
[0099] 3) Sodium carbonate, analytical grade;
[0100] 4) Calcium carbonate, analytical grade;
[0101] 5. Raw material expansive agent:
[0102] 1) Water, tap water;
[0103] 2) Water-reducing agent aqueous solution, polycarboxylate water-reducing agent;
[0104] 3) Water-reducing agent aqueous solution, naphthalene-based water-reducing agent;
[0105] The performance testing method of this invention:
[0106] The performance of the obtained solid waste-based ceramsite was tested according to the method specified in GB / T17431-2010 to obtain the compressive strength, bulk density and water absorption rate of the obtained solid waste-based ceramsite.
[0107] Example 1 (S1)
[0108] Solid waste-based ceramsite A1 was prepared according to the following method, including:
[0109] (1) All raw materials other than the raw material expansion agent are crushed and ground to below 150 mesh. The aluminum silicon mineral material (coal gangue with an organic matter content of 9.31%), carbon silicon composite material (gasification fine slag), and pore conditioner (red mud) are mixed in proportion by weight and then placed in a mixer to obtain a mixture.
[0110] (2) The mixture obtained in step (1) is mixed with the raw material expansive agent (water) according to the weight ratio and placed into an extrusion granulator for mixing, granulation and polishing. The polishing speed is 800 rpm / min and the polishing time is 15 min to obtain ceramsite raw material balls.
[0111] The raw materials for preparation are proportioned in the following order: aluminum-silicon mineral materials (coal gangue), carbon-silicon composite materials (gasification fine slag), pore regulator (red mud), and raw material expansion agent (water) in the following weight ratios: 70, 29, 1, and 9, respectively.
[0112] (3) Place the ceramsite raw pellets obtained in step (2) in an oven for drying treatment at 40°C for 8 hours to obtain dried raw pellets;
[0113] (4) The dried raw material balls obtained in step (3) are placed in a muffle furnace for calcination treatment, including a first stage and a second stage. In the first stage, the temperature is increased by 3℃ / min and stopped at 450℃. After 60min, the second stage is carried out. In the second stage, the temperature is increased by 10℃ / min and stopped at 1000℃. After 45min, the furnace is cooled to room temperature to obtain solid waste-based ceramsite A1.
[0114] Example 2 (S2)
[0115] Solid waste-based ceramsite A2 was prepared according to the preparation method of Example 1 (S1), wherein the only difference from Example 1 (S1) is:
[0116] In step (1), a plasticity modifier (slag) was added to the raw materials; and
[0117] In steps (1) and (2), the raw materials are prepared in the following proportions: aluminum silicon mineral material (coal gangue with an organic matter content of 9.31%), carbon silicon composite material (high carbon coal gangue), plasticity regulator (slag), pore regulator (red mud), and raw material expansion agent (water) in the following weight proportions: 85, 12, 2, 1, and 28.5, respectively.
[0118] In step (3), the drying process involves baking at 70°C for 6 hours;
[0119] In step (4), the first stage is to raise the temperature by 4℃ / min until it reaches 500℃ and then stop heating. After 45 minutes, the second stage is carried out. The second stage is to raise the temperature by 15℃ / min until it reaches 900℃ and then stop heating. After 60 minutes, the furnace is cooled to room temperature.
[0120] Example 3 (S3)
[0121] Solid waste-based ceramsite A3 was prepared according to the preparation method of Example 1 (S1), wherein the only difference from Example 1 (S1) is:
[0122] In step (1), a plasticity modifier (clay) was added to the raw materials, and
[0123] In steps (1) and (2), the raw materials are prepared in proportions of 94, 4, 1, 1, and 26 by weight of aluminum silicon mineral material (coal gangue with an organic matter content of 9.31%), carbon silicon composite material (gasification fine slag), plasticity regulator (clay), pore regulator (sodium carbonate), and raw material expansion agent (water).
[0124] In step (3), the drying process involves baking at 60°C for 12 hours;
[0125] In step (4), the first stage is to raise the temperature by 3℃ / min until it reaches 400℃ and then stop heating. After 75 minutes, the second stage is carried out. The second stage is to raise the temperature by 15℃ / min until it reaches 850℃ and then stop heating. After 75 minutes, the furnace is cooled to room temperature.
[0126] Example 4 (S4)
[0127] Solid waste-based ceramsite A4 was prepared according to the preparation method of Example 1 (S1), wherein the only difference from Example 1 (S1) is:
[0128] In steps (1) and (2), the raw materials are prepared according to the following weight ratios: aluminum silicon mineral material (coal gangue with an organic matter content of 9.31%), carbon silicon composite material (gasification fine slag), pore regulator (red mud), and raw material expansion agent (water) in the following proportions: 90, 5, 5, and 23 respectively.
[0129] In step (3), the drying process involves baking at 40°C for 24 hours;
[0130] In step (4), the first stage is to raise the temperature by 3℃ / min until it reaches 300℃ and then stop heating. After 90 minutes, the second stage is carried out. The second stage is to raise the temperature by 15℃ / min until it reaches 1000℃ and then stop heating. After 30 minutes, the furnace is cooled to room temperature.
[0131] Example 5 (S5)
[0132] Solid waste-based ceramsite A5 was prepared according to the preparation method of Example 1 (S1), wherein the only difference from Example 1 (S1) is:
[0133] In step (1), a plasticity modifier (slag) was added to the raw materials; and
[0134] In steps (1) and (2), the raw materials are prepared in the following proportions: aluminum-silicon mineral material (kaolin, organic matter content 5.89%), carbon-silicon composite material (coal slime), plasticity regulator (slag), pore regulator (hematite), and raw material expansion agent (water-reducing agent aqueous solution, specifically carboxylic acid water-reducing agent aqueous solution, concentration 15%), with weight ratios of 70, 15, 5, 10, and 1 respectively.
[0135] In step (3), the drying process involves baking at 50°C for 10 hours;
[0136] In step (4), the first stage is to raise the temperature at 3.5℃ / min until it reaches 300℃ and then stop heating. After 25 minutes, the second stage is carried out. The second stage is to raise the temperature at 5℃ / min until it reaches 700℃ and then stop heating. After 90 minutes, the furnace is cooled to room temperature.
[0137] Example 6 (S6)
[0138] Solid waste-based ceramsite A6 was prepared according to the preparation method of Example 1 (S1), wherein the only difference from Example 1 (S1) is:
[0139] In step (1), a plasticity modifier (slag) was added to the raw materials; and
[0140] In steps (1) and (2), the raw materials are prepared in the following proportions: aluminum-silicon mineral material (bentonite, organic matter content 4.76%), carbon-silicon composite material (coal slime), plasticity regulator (slag), pore regulator (calcium carbonate), and raw material expansion agent (water-reducing agent aqueous solution, specifically naphthalene-based water-reducing agent aqueous solution, concentration 32%), with weight ratios of 79, 9, 10, 2, and 15 respectively.
[0141] In step (4), the first stage is to raise the temperature by 4℃ / min until it reaches 500℃ and then stop heating. After 10 minutes, the second stage is carried out. The second stage is to raise the temperature by 5℃ / min until it reaches 900℃ and then stop heating. After 90 minutes, the furnace is cooled to room temperature.
[0142] Example 7 (S7)
[0143] Solid waste-based ceramsite A7 was prepared according to the preparation method of Example 1 (S1), wherein the only difference from Example 1 (S1) is:
[0144] In step (1), a plasticity modifier (slag) was added to the raw materials; and
[0145] In steps (1) and (2), the raw materials are prepared in proportions of 70, 19, 10, 1 and 9 respectively, consisting of aluminum-silicon mineral material (coal gangue with an organic matter content of 9.31%), carbon-silicon composite material (gasification fine slag), plasticity regulator (clay), pore regulator (red mud), and raw material expansion agent (water).
[0146] Comparative Example 1 (D1)
[0147] Solid waste-based ceramsite A1' was prepared according to the preparation method of Example 1 (S1), wherein the only difference from Example 1 (S1) is:
[0148] In step (1), the raw materials are prepared in proportions of 30, 70, and 1 by weight of aluminum silicon mineral material (coal gangue with an organic matter content of 9.31%), carbon silicon composite material (gasification fine slag), and raw material expansion agent (water).
[0149] Comparative Example 2 (D2)
[0150] Solid waste-based ceramsite A2' was prepared according to the preparation method of Example 1 (S1), wherein the only difference from Example 1 (S1) is:
[0151] In step (1), the organic matter content of the aluminum-silicon mineral material - coal gangue is 2.18%.
[0152] Comparative Example 3 (D3)
[0153] Solid waste-based ceramsite A3' was prepared according to the preparation method of Example 1 (S1), wherein the only difference from Example 1 (S1) is:
[0154] In step (1), the organic matter content of the aluminum-silicon mineral material - coal gangue is 2.18%;
[0155] In step (3), the drying process involves baking at 120°C for 1 hour;
[0156] In step (4), the first stage is to raise the temperature by 20℃ / min until it reaches 500℃ and then stop heating. After 30 minutes, the second stage is carried out. The second stage is to raise the temperature by 20℃ / min until it reaches 1120℃ and then stop heating. After 30 minutes, the furnace is cooled to room temperature.
[0157] Comparative Example 4 (D4)
[0158] Solid waste-based ceramsite A4' was prepared according to the preparation method of Example 1 (S1), wherein the only difference from Example 1 (S1) is:
[0159] In step (1), no carbon-silicon composite material (gasification fine slag) was added to the raw materials; and
[0160] In steps (1) and (2), the raw materials are prepared in proportions of 99, 1, and 9 by weight of aluminum-silicon mineral material (coal gangue with an organic matter content of 9.31%), pore conditioner (red mud), and raw material expansion agent (water).
[0161] Comparative Example 5 (D5)
[0162] Solid waste-based ceramsite A5' was prepared according to the preparation method of Example 1 (S1), wherein the only difference from Example 1 (S1) is:
[0163] In steps (1) and (2), the raw materials are prepared in proportions of 69, 30, 1, and 11 by weight of aluminum silicon mineral material (coal gangue with an organic matter content of 9.31%), carbon silicon composite material (gasification fine slag), pore conditioner (red mud), and raw material expansion agent (water).
[0164] Comparative Example 6 (D6)
[0165] Solid waste-based ceramsite A6' was prepared according to the preparation method of Example 1 (S1), wherein the only difference from Example 1 (S1) is:
[0166] In steps (1) and (2), the raw materials are prepared in proportions of 69, 30, 1, and 11 by weight of aluminum silicon mineral material (coal gangue with an organic matter content of 9.31%), carbon silicon composite material (gasification fine slag), pore regulator (red mud), and raw material expansion agent (water).
[0167] In step (3), the drying process involves baking at 120°C for 1 hour;
[0168] In step (4), the first stage is to raise the temperature by 20℃ / min, stop heating at 500℃, maintain for 30min, and then cool down to room temperature with the furnace; the second stage is to raise the temperature by 20℃ / min, stop heating at 1120℃, maintain for 30min, and then cool down to room temperature with the furnace.
[0169] Performance test results
[0170] The solid waste-based ceramsite obtained from Examples 1-7 (S1-7) and Comparative Examples 1-6 (D1-6) was subjected to performance tests to obtain its compressive strength, bulk density and water absorption rate. The performance test results are shown in Table 1.
[0171] Table 1 shows the performance test results of the solid waste-based ceramsite.
[0172]
[0173]
[0174] Based on the comparison between the embodiments and the comparative examples, and the data in Table 1, it can be seen that:
[0175] Under the preparation raw material ratio and requirements of the present invention, solid waste-based ceramsite that meets the performance requirements can be obtained only at low temperature and low energy consumption; however, under the preparation raw material ratio and requirements that do not meet the present invention, solid waste-based ceramsite that meets the performance requirements cannot be obtained at low temperature and low energy consumption, and can only be obtained at high temperature and high energy consumption.
Claims
1. A solid waste-based ceramsite, characterized in that, The raw materials for preparing the solid waste-based ceramsite include the following substances in parts by weight: Aluminosilicate mineral materials 70-95; Carbon-silicon composite material 4-29; Pore conditioner 1-10; Raw material expansion agent 1-30.
2. The solid waste-based ceramsite according to claim 1, characterized in that, The raw materials also include a plasticizer, wherein the plasticizer has a weight ratio of ≤10 parts.
3. The solid waste-based ceramsite according to claim 1 or 2, characterized in that, The silicon-aluminum mineral material has a SiO2 / Al2O3 content ratio ≥ 1.2, and / or a total SiO2 and Al2O3 content ≥ 70%; and / or a total carbon content ≤ 15%, and / or an organic matter content ≥ 4%; and / or The silica-aluminate mineral material includes any one or a combination of coal gangue, kaolin, and bentonite.
4. The solid waste-based ceramsite according to any one of claims 1-3, characterized in that, In the aforementioned carbon-silicon composite material, the total dry-basis SiO2 content is ≥30%, and / or the carbon content is ≥15%, and / or the iron oxide content is ≥3%; and / or, The carbon-silicon composite material includes any one or more combinations of gasification slag, high-carbon coal gangue, coal slime, and silicon carbide.
5. The solid waste-based ceramsite according to claim 2, characterized in that, The plasticity modifier has a plasticity index ≥10 and / or a particle size D. 90 ≤100μm, and / or the calcium oxide content therein is ≥3%; and / or, The plasticity modifier includes slag and / or clay.
6. The solid waste-based ceramsite according to any one of claims 1-5, characterized in that, The pore conditioner includes a first pore conditioner and / or a second pore conditioner; The first pore conditioner contains ≥10% Fe2O3; and / or the first pore conditioner includes red mud and / or hematite; The second pore conditioner includes carbonates.
7. The solid waste-based ceramsite according to any one of claims 1-6, characterized in that, The raw material expansive agent includes water and / or an aqueous solution of a water-reducing agent.
8. A method for preparing the aforementioned solid waste-based ceramsite, characterized in that, The preparation method includes: (1) After crushing and grinding all the raw materials except the raw material expansive agent, they are mixed according to the weight ratio to obtain a mixture; (2) The mixture obtained in step (1) is mixed with the raw material expansion agent according to the weight ratio, granulated and polished to obtain ceramsite raw material balls; (3) The ceramsite raw material balls obtained in step (2) are dried to obtain dried raw material balls; (4) The dried raw material balls obtained in step (3) are calcined to obtain solid waste-based ceramic particles.
9. The preparation method according to claim 8, characterized in that, In step (3), the drying process involves placing the ceramsite raw pellets obtained in step (2) in an oven at 40-70℃ for 4-24 hours.
10. The preparation method according to claim 8 or 9, characterized in that, In step (4), the calcination treatment includes a first stage and a second stage; In the first stage, the calcination temperature is 300-500℃, and / or the calcination time is 10-90 min; and / or the heating rate is 3-5℃ / min; and / or, In the second stage, the calcination temperature is 700-1000℃, and / or the calcination time is 30-90 min; and / or the heating rate is 5-15℃ / min.